Efectos de la inversión pública en educación primaria sobre la calidad educativa en la región Loreto periodo 2009–2019 - Cavallier Martinez, Astrid Stephanie (2022)
In this thesis, we seek to validate how important is the role of the Peruvian Government on the development of educational quality in the department of Loreto; This is done through approaches to econometric models that reflect Loreto's public investment in the primary education sector (both at the aggregate level and by government level) as an exogenous variable that can cause Granger-like behavior in the quality of education (measured through the average percentage of second grade elementary school students who achieved a satisfactory level in reading comprehension and mathematical reasoning) of the department of Loreto. The results show that public investment in primary education does have positive and significant effects on the educational quality of the Loreto region. In particular, it is validated that if the aggregate public investment increases by 1%, this generates that the educational quality in reading comprehension and mathematical reasoning increases by 1.83% and 1.18%, respectively.